Edukasi Penanganan Sampah Rumah Tangga di Wilayah Denpasar Selatan - Luh Putu Eka Yuni Suntari; Ni Gusti Ayu Agung Seri Widi Antari; Ni Kadek Desnita Pradnya Dewi Mas; Kristianus Angga Saputra Mbosi; Maria Isadela Busu; Ni Kadek Yudia Kristina; Ni Luh Putu Ning Septyarini Putri Astawa; Putu Devangga Makarabaja (PROGRESIF: Jurnal Pengabdian Komunitas Pendidikan, 2026)
Household waste management in densely populated residential areas remains a challenge due to low public awareness of waste sorting and limited access to educational media. This community service program aimed to improve the knowledge and awareness of residents of Gang XXR No. 8, Banjar Bekul, Panjer, regarding household waste management. The program employed the design thinking approach, consisting of the empathize, define, ideate, prototype, and test stages. Activities included the development and installation of infographic posters equipped with QR Codes linked to waste-sorting tutorial videos. The posters were placed at waste disposal sites, while the videos were distributed through the community WhatsApp group. The results showed increased access to waste management information, improved awareness of waste sorting, and positive responses from residents. The findings suggest that simple technology-based visual media combined with community communication channels can effectively support environmental education and promote better household waste management practices.